Prevalence and location of myofascial trigger points in dogs with osteoarthritis - Formenton, Maira Rezende; Fantoni, Denise Tabacchi; Gauthier, Lisa; Cachon, Thibaut; Yeng, Lin Tchia; Portier, Karine (Frontiers in Veterinary Science, 2025)
IntroductionThis study was designed to determine the prevalence of myofascial pain and the location of myofascial trigger points (MTPs) in dogs with osteoarthritis.MethodsThirty-five dogs were selected and examined for the presence of MTPs using palpation. Assessments were performed independently by two examiners. Correlations between age, MTP number and location, and the site of osteoarthritis were also investigated.Results and discussionThirty out of 35 dogs (86%) had at least one MTP and only 5 (14%) had none. A total of 177 MTPs were identified in dogs in this sample. The prevalence of MTPs was higher in the longissimus thoracicae (40% and 43%; left and right side respectively), followed by the quadriceps femoris (40% and 31%), longissimus lumborum (20% and 23%), gluteus medius and deltoid muscles (14%; left side only), and the pectineus muscle (11%; right side only). The number of osteoarthritic joints was not correlated with the number of MTPs or age. However, age was positively correlated with the number of muscles affected by MTPs. Correlations between the presence of MTPs in muscles surrounding and the affected joints were also lacking.ConclusionThe prevalence of MTPs in dogs with osteoarthritis is high. Myofascial TPs are positively correlated with age in these patients. The subjective nature of palpation is a major limitation in myofascial pain assessment. Appropriate training and use of standardized diagnostic criteria are recommended.